PENDIDIKAN PARENTING PRANIKAH: Upaya Perbaikan Generasi Berkualitas - Khairun Nisa (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
Current life reality has indicated the phenomenon of modern human who have distance from their spiritual awareness. This cannot be separated from the role of parents whose primary task to plant religious values in their family members. Families who are aware of the importance of religious education in the life of their children will definitely create persons with strong spiritual defence towards the challanges of modernity. Conversely, otherwise. Parents is the most influen-tial party in the successfull development of children. However, many parent are currently not aware of their significant role in the personality development of their children. Many parent completely entrust the education of their children to particular school institutions without reliable synergy between the educational institutions and parents for the education of children. As the parenting concept is aimed at preparing strong and high quality generation, it is absolutely important for parents to build their self-capacity with parenting education. This is because in Islamic education, the parenting education is closely linked to pre-conception, pre-natal, and post-natal educations. Therefore, parent candidates must have parenting education in order to generate strong and high quality generations.